2021
DOI: 10.2147/ndt.s283558
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Experience and Intervention in Post-Acute COVID-19 Inpatients

Abstract: Purpose COVID-19 patients faced first-hand the life-threatening consequences of the disease, oftentimes involving prolonged hospitalization in isolation from family and friends. This study aimed at describing the psychological intervention to address the psychological difficulties and issues encountered by the hospitalized post-acute COVID-19 patients in a rehabilitation setting. Patients and Methods Patients’ demographics, medical diagnosis, and neuro-psychological inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 62 publications
4
33
0
1
Order By: Relevance
“…According to literature (e.g., Bonanno & Diminich, 2013) [ 73 ], age may have a curvilinear relationship with resilience, with the younger and elder individuals at higher risk for psychological issues [ 74 76 ]. Thus, particular attention should be dedicated to individuals with unfavourable conditions and the already vulnerable groups, as great elderlies [ 63 , 77 ], patients with pre-existing medical diseases–e.g., cardiac, oncological [ 26 , 75 , 78 82 ], and health-care professionals [ 83 , 84 ] for which the COVID-19 may have increased the risk of developing dangerous consequences and detrimental effects on both physical and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…According to literature (e.g., Bonanno & Diminich, 2013) [ 73 ], age may have a curvilinear relationship with resilience, with the younger and elder individuals at higher risk for psychological issues [ 74 76 ]. Thus, particular attention should be dedicated to individuals with unfavourable conditions and the already vulnerable groups, as great elderlies [ 63 , 77 ], patients with pre-existing medical diseases–e.g., cardiac, oncological [ 26 , 75 , 78 82 ], and health-care professionals [ 83 , 84 ] for which the COVID-19 may have increased the risk of developing dangerous consequences and detrimental effects on both physical and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the social desirability of respondents may have influenced their answers to the structured clinical interview. Additionally, despite the fact that administered structured interview showed good psychometric properties with good "infit" and "outfit" indices, the unfavorable environmental conditions (i.e., hygienic reasons) did not allow the use of any further assessment tool such as self-report questionnaires [8]. Still, the clinical interview allowed one to simultaneously investigate the three basic components for effective communication: verbal (i.e., the content of the message), non-verbal; (i.e., body language such as posture, gesture, facial expression, and spatial distance), and para-verbal (i.e., including tone, pitch, pacing and volume of the voice).…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous research [8,44,80], due to the impossibility of using routinely paper-and-pencil assessment questionnaires, an ad hoc structured interview was created for this study and administered to oncological outpatients. The use of a structured interview was deemed appropriate to allow the investigation of the patients' thoughts, emotions, and psychological issues using standardized methodological procedures [8].…”
Section: Measures: (Development Of) the Structured Interviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most of the literature highlighted the negative impact of COVID-19 for health professionals (Benfante et al, 2020;Pappa et al, 2020), this study is one of the few trying to also consider the positive and protective factors as esteem, resilient coping, and the positivity of the experience (Rieckert et al, 2021). Recent studies also showed that the COVID-19 pandemic implied a severe psychological burden for health workers, but also COVID-19 patients and caregivers and the general population as well (Bruno et al, 2020;Nese et al, 2020;Panzeri and Rossi Ferrario, 2020;Parola et al, 2020;Que et al, 2020;Rossi Ferrario et al, 2021). Despite this fact, a significant number of people avoided seeking social support and/or professional psychological help (Ratti et al, 2017;Rossi and Mannarini, 2019), probably due to the associated social and personal stigma (Mannarini et al, 2018(Mannarini et al, , 2020Mannarini and Rossi, 2019).…”
Section: Discussionmentioning
confidence: 88%